Formation of repetitively pulsed high-intensity, low-energy silicon ion beams; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 953 - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Dektyarev S. V. Sergey Valentinovich; Shevelev A. E. Aleksey Eduardovich (2020, 2020)
Title screen